Modified poly(L-lysine)-based structures as novel antimicrobials for diabetic foot infections, an in-vitro study [version 1; peer review: 2 approved] - Alicia Grace; Aoife Dillon; Robert Murphy; Sally-Ann Cryan; Diarmuid Smith; Deirdre Fitzgerald-Hughes; Andreas Heise (HRB Open Research, 2022)
Background: Wound infections occur as sequelae to skin trauma and cause significant hospitalizations, morbidity and mortality. Skin traumas arise more frequently in those with diabetes or cardiovascular disease and in these settings, may be chronic with poorer outcomes including lower limb amputation. Treatment of chronic wound infection is challenging due to antibiotic resistance and biofilm formation by bacteria including S. aureus and P. aeruginosa, which are among the most frequent causative pathogens. Managing these challenging infections requires new molecules and modalities. Methods: We evaluated antimicrobial and anti-biofilm activity of star-shaped poly(L-lysine) (PLL) polymers against S. aureus and P. aeruginosa strains and clinical isolates recovered from wounds including diabetic foot wounds (DFW) in a Dublin Hospital in 2019. A star-shaped PLL polypeptide series, specifically G2(8)PLL20, G3(16)PLL10, G4(32)PLL5 with variation in polypeptide chain length and arm-multiplicity, were compared to a linear peptide, PLL160 with equivalent number of lysine residues. Results: All PLLs, including the linear polypeptide, were bactericidal at 1μM against S. aureus 25923 and P. aeruginosa PAO1, with log reduction in colony forming units/ml between 2.7-3.6. PLL160 demonstrated similar killing potency against 20 S. aureus and five P. aeruginosa clinical isolates from DFW, mean log reductions: 3.04 ± 0.16 and 3.96 ± 0.82 respectively after 1 hour incubation. Potent anti-biofilm activity was demonstrated against S. aureus 25923 but for clinical isolates, low to moderate loss of biofilm viability was shown using PLL160 and G3(16)PLL10 at 50 μM (S. aureus) and 200 μM (P. aeruginosa) with high inter-isolate variability. In the star-shaped architecture, antimicrobial activity was retained with incorporation of 5-mer hydrophobic amino-acid modifications to the arms of the polypeptides (series G3(16)PLL20-coPLT5, G3(16)PLL20-coPLI5, G3(16)PLL20-coPLP5). Conclusion: These polypeptides offer structural flexibility for clinical applications and have potential for further development, particularly in the setting of diabetic foot and other chronic wound infections.